ASSOCIATION OF IRON DEFICIENCY ANEMIA WITH ACUTE LOWER RESPIRATORY TRACT INFECTIONS IN CHILDREN - Nawaz, Raazia; Hussain, Shabbir; Khushdil, Arshad; Tanveer, Sidra; Javed, Maria; Akram, Saira (Pakistan Armed Forces Medical Journal, 2021)
Objective: To establish association between acute lower respiratory tract infection and iron deficiency anemia. Study Design: Case-control study. Place and Duration of Study: Pediatrics Department, Pak Emirates Military Hospital, Rawalpindi, from Dec 2017 to May 2018. Methodology: A total of 100 children with age ranging from 6-60 months were selected for this study with 50 being in each group. Study group constituted of children presenting with acute lower respiratory tract infection and healthy children presenting to outpatient were taken as controls. Hemoglobin levels (<11g/dl), mean corpuscular volume (<70fl), Serum Ferritin (<30ng/ml) and red blood cell Morphology were used to determine iron deficiency anemia. Patients meeting the WHO criteria were labeled to have acute lower respiratory tract infection. Results: The frequency of iron deficiency was found to be 40 (80%) in cases and only 34 (17%) in healthy controls. A significant association was found between iron deficiency anemia and acute lower respiratory tract Infection with an odds ratio of 7.76 and a significant p-value of <0.01. Conclusions: Iron deficiency anemia has an increased association of up to seven times in children with acute lower respiratory tract infections as compared to healthy children thus highlighting it as a significant risk factor.